Approaches for the assembly simulation of skin model shapes. (August 2015) - Schleich, Benjamin; Wartzack, Sandro
Abstract: Even though they are weakly noticed, geometric part deviations accompany our everyday life. These geometric deviations affect the assemblability and functional compliance of products, since small part variations accumulate through large-scale assemblies and lead to malfunction as well as decreased product reliability and safety. However, the consideration of part deviations in the virtual modelling of mechanical assemblies is an ongoing challenge in computer-aided tolerancing research. This is because the resulting assembly configurations for variant parts are far more complicated than for nominal assemblies. In this contribution, two approaches for the relative positioning of point based models are highlighted and adapted to the assembly simulation of Skin Model Shapes, which are specific workpiece representatives considering geometric deviations. The first approach employs constrained registration techniques to determine the position of variant parts in an assembly considering multiple assembly steps simultaneously, whereas the second utilizes the difference surface to solve the positioning problem sequentially. The application of these approaches to computer-aided tolerancing is demonstrated, though their applicability reaches various fields of industrial geometry. Highlights: Skin Model Shapes are digital part representatives comprising geometric deviations. Approaches for the relative positioning of point-based Skin Model Shapes are proposed. The approaches ground on algorithms from computational geometry and computer graphics. Applications for the assembly simulation in tolerancing are given.